(3GdGSJKeGQ GdOhdjI (B:s (3GdJMcje GdJLGQj GdOhdj VeGf GdGSJKeGQGJ (B/s - (3bGOQj, YHO GdYRjRs ((3GdLRGFQ(B: s (3OGQ gheI(B, s, 2004)
(3aj gPG GdcJGH (B: 1- (3ebOeI (B2- (3GdGSJKeGQGJ GdOhdjI GdeHGTQI GdJfXjeGJ hGdJWhQGJ (B3- (3GdJMcje aj eLGd GdGSJKeGQGJ GdOhdjI GdJMcje GdJLGQj (B4- (3VeGf GdGSJKeGQGJ GdOhdjIs
Keywords: (3GSJKeGQ Ohdjs; (3GdGSJKeGQs; (3GdbGfhf GdOhdj GdJLGQjs; (3bGfhf Ohdjs